Upaya Penegakan Hukum Terkait Pertambangan Emas Tanpa Izin yang Mengakibatkan Delapan Pekerja Meninggal Dunia di Ajibarang - Abdilah, Muhamad Shafri (Proceedings Series on Social Sciences & Humanities, 2024)
The rise of illegal gold mining activities, especially those carried out in Ajibarang, cannot be separated from various factors that cause illegal gold mining activities, including social, legal and economic factors. In preparing this legal research, normative juridical methods are used with qualitative analysis by collecting data such as observation, visual analysis, literature study. The data collected will be analyzed to draw conclusions in this research. The findings obtained are, there are still illegal gold mining perpetrators who enter from the rat roads around Mount Botak, there are overlapping mining permits, there is no synergy between law enforcement officials in dealing with criminal acts in the mining sector, there is still a lack of public awareness of the impact of mining. Traditionally, the environment is polluted due to the disposal of mercury and cyanide waste. As a result of this pollution, several babies are born with disabilities, both structurally in the form of physical abnormalities and functional disabilities such as Down syndrome. This disability occurred because while the mother was pregnant she consumed water that was contaminated with mercury and cyanide waste. This article aims to describe efforts to control illegal gold mining activities in Ajibarang Regency.